Seasonal variation of macroinvertebrates in the estuary ecosystem: A case study of Mae Klong and Tha Chin Estuaries, the Upper Gulf of Thailand - Kulabtong, S.; Wattana, K.; Charroenmoon, K.; Bamrung, P.; Petsut, N. (International Journal of Agricultural Technology, 2021)
A seasonal variation of macroinvertebrates in the estuary ecosystem was reported. The results showed a basic information in natural resource management planning and benefits to local people. Macroinvertebrate variation was recorded at Mae Klong Estuary and Tha Chin Estuary in the Upper Gulf of Thailand. Four stations of two estuaries were sampled in three seasons: January 2017 (winter representative), April 2017 (summer representative) and September 2017 (rainy season representative). A total of 29 species of macroinvertebrates were recorded. Malacostraca was the dominant species number (9 species), and the highest quantity (40-54 % of all specimen). Metapenaeus was the dominant species (24 %). The density of macroinvertebrate tended to increase in the winter. Also, the density droped to the lowest during the summer. The ecological indices of macroinvertebrates in each season were not statistically significant difference (p>0.05). The diversity index was 1.76-1.97, the evenness index was 0.25-0.32, and the dominance index was 0.68-0.75. It is explained that in each season, some groups of macroinvertebrate were more prominent than other groups. The relationship between the average total density of macroinvertebrates and water quality factors showed a moderate level of correlation (r = -0.622) and a statistical significance (p<0.05) with temperature